2018
DOI: 10.1002/oby.22314
|View full text |Cite
|
Sign up to set email alerts
|

Youth Subjective Social Status (SSS) is Associated with Parent SSS, Income, and Food Insecurity but not Weight Loss Among Low‐Income Hispanic Youth

Abstract: Objective: Subjective social status (SSS), perceived rank in the social ladder, is associated with weight, but determinants of SSS in youth remain unknown. We investigated relationships between youth SSS and income, food insecurity, parent SSS, and BMI change during an obesity intervention. Methods: Data came from a family-centered, community-based obesity intervention for low-income families. Parent and youth SSS were assessed using a validated, age-appropriate SSS scale. Food insecurity and socioeconomic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…In the linear regression model, adjustments were made stepwise in major groups, which did not reveal which variable contributed the most to confounding. Subanalyses showed that self-rated health and SSS (SSS in school if the exposure was SSS in society and vice versa) were the main contributors to confounding (data not shown).Additionally, the FOCA cohort did unfortunately not provide data to include previously found potential confounders in adolescents populations as objective measures of SES and parent SSS [12,38].…”
Section: Strength and Limitationmentioning
confidence: 98%
“…In the linear regression model, adjustments were made stepwise in major groups, which did not reveal which variable contributed the most to confounding. Subanalyses showed that self-rated health and SSS (SSS in school if the exposure was SSS in society and vice versa) were the main contributors to confounding (data not shown).Additionally, the FOCA cohort did unfortunately not provide data to include previously found potential confounders in adolescents populations as objective measures of SES and parent SSS [12,38].…”
Section: Strength and Limitationmentioning
confidence: 98%
“…Cardel et al (1) found that the BMI percent of the 95th percentile among youth with overweight and obesity decreased significantly after 6 weeks of intervention. By choosing to report the BMI percent of the 95th percentile, the authors avoided the impracticality of using changes in BMI percentile among youth with extreme BMI (3).…”
Section: Obesitymentioning
confidence: 99%
“…The Relationship Between Youth Subjective Social Status (SSS) and Weight Loss Rena C. Moon TO THE EDITOR: Socioeconomic status (SES) is known to have an inverse relationship with childhood obesity; lower SES has been linked to higher prevalence of obesity and poorer weight loss after obesity interventions among children (1,2). However, evidence suggests that the effect of SES on childhood obesity is modified by other factors (i.e., race and gender), indicating a more complicated relationship between the two (2).…”
Section: Obesitymentioning
confidence: 99%
See 2 more Smart Citations